Comparação da fauna de Cerambycidae (Coleoptera) entre um fragmento de Cerrado Regenerante e uma área antropizada dentro do campus da Unesp em Rio Claro, SP, Brasil - Clemente, Mateus Aparecido; D’Tódaro, Ariane [UNESP]; Giannotti, Edilberto [UNESP] (Lepidus Tecnologia, 2023)
Cerambycidae is a family of Coleptera with great ecological and economic importance. Because they are intimately involved in various ecological processes, individuals in this family have an excellent bioindicator potential. In this work, two areas with different levels of anthropic disturbance were compared within the Unesp campus of Rio Claro, SP, Brazil. A total of 92 individuals were distributed in 2 subfamilies, 8 tribes, 14 genera and 17 species captured in 8 collections carried out between May 2015 and January 2016. The abundance and richness of collected species were used to compare the two areas within the campus, one of Regenerating cerrado and less anthropized (Area A) and a more anthropized area, near the campus buildings (Area B). After analysis of their variables, the areas were similar. Two-color traps (red and transparent) installed in two different vegetation strata (diameter at breast height (DAP) and canopy were used. The abundance and richness of species captured by each trap were compared. Canopy traps, regardless of their color, proved to be more efficient in capturing abundance. The climatic variables (temperature, rainfall, and relative humidity) and their oscillations recorded in the time interval studied were also analyzed.